A review of the tribe Noviini (Coleoptera: Coccinellidae) of the Indian subcontinent - Poorani, J. (Zootaxa, 2023)
The tribe Noviini (Coleoptera: Coccinellidae) is economically important as its members are mainly predators of giant scales belonging to the family Monophlebidae and occasionally, mealybugs (Pseudococcidae). At present, 17 species of the tribe, all belonging to the sole recognized genus Novius Mulsant, are known from the Indian region. An illustrated account of the Indian species of Novius is presented here with brief diagnostic accounts, illustrations of the genitalia and details on the distribution, host insects and associated host plants. Life stages of the species are also illustrated wherever available. An updated checklist of Novius species of the Indian subcontinent is provided.